The Effect of Web Based Corporate Reporting on Company Value - Mutiara Tresna Parasetya; Andrian Budi Prasetyo; Aditya Septiani; Muchamad Syafruddin (Eduvest - Journal of Universal Studies, 2022)
Very fast developments in technology have encouraged companies in the world to convey and disseminate corporate information globally in the form of web-based corporate reporting. Based on data from internet users, Indonesia is the fourth largest country in the world as internet users, and the majority of internet users in Indonesia are entrepreneurs. This shows that the company conducts web-based corporate reporting with the aim of attracting potential investors. Web-based corporate reporting is carried out by the company as a form of information disclosure and this will affect the value of the company. This study examines the effect of the level of web-based corporate reporting on firm value, and examines what information is needed by investors in making decisions to invest in a company. This study focuses on banking companies as a tertiary sector and uses multiple regression analysis in the test. This study found that the information disclosed on the company's website, especially related to stock information, had a significant positive effect on firm value.